Analysis of defects in coffee beans compared to biplots forsimultaneous tables - Guimarães Brighenti, Carla Regina; Cirillo, Marcelo Angelo (Revista Ciência Agronômica, 2023)
The demand for high quality coffee has become a consolidated criterion to achieve the best prices. Currently,cooperatives evaluate the coffee beans mainly through the particle size and the number of defects in the sample. This evaluationtype generates counting data that originates contingency tables from different periods or groups involving the same variablesin the row and column and there may be interest in knowing if two tables are related and how much are related. Theseare the so-called combined tables. Statistical analysis techniques normally employed do not include categorical data in thecombined tables. The aim of this study was to evaluate the incidence of different types of defects in samples of large flat coffeebeans in two different harvests through the construction of biplots. The decomposition theory in single simultaneous values ofdouble entry contingency tables was used. The results of defect counting in beans of 24 coffee samples from southern MinasGerais, Brazil, were evaluated in the 2014 and 2015 harvests. Moreover, the association among defect types, considered withindifferent total defect proportions in the sample, was verified based on the percentage in 17/18 sieves. It was also evaluated therelative sums of squares from the similarity and dissimilarity among the harvests. It is concluded that the simultaneous analysistechnique allows better visualizing the common behavior and alterations among different harvests, distinguishing the defecttypes associated with each harvest and among different proportions of large flat beans.